Assessing the Syrian Population’s Knowledge, Attitudes, and Practices Regarding Antibiotic Usage - Altorkmani, Abdallah; Alzabibi, Mhd Amin; Shibani, Mosa; Ismail, Hlma; Sawaf, Bisher; Daher, Nizar; Al-Moujahed, Ahmad (Avicenna Journal of Medicine, 2021)
Background Antibiotic resistance is a serious public health threat that results mainly secondary to antibiotics misuse. The present study aimed to determine the knowledge, attitude, and practice toward antibiotic use among the Syrian population.Methods This cross-sectional study was conducted at the outpatient clinics of two major hospitals in Damascus, Syria. Applying a random convenience sampling, data were collected in a 1-week period by interviewing participants using a structured questionnaire, which targeted demographics, practice, knowledge, and attitude. Data were used to assess the relationship between the knowledge level and attitudes and demographics.Results Most respondents had a moderate level of knowledge (187, 74.8%) and a moderate attitude score (148, 59.2%). In addition, most respondents (149, 59.6%) stated that they take antibiotics based on pharmacist advice only and do not complete the full antibiotic course (200, 80%). A significant association was found between the knowledge level and financial status (p-value = 0.003), education level (p-value = 0.001), and having relatives working in the health care sector (p-value = 0.021). In addition, a significant association was found between the attitude and having health insurance.Conclusion This study provides baseline evidence about the knowledge, attitudes, and practices regarding antibiotics among the Syrian population, that will help in designing targeted interventions to solve the inappropriate use of antibiotics.
Keywords: antibiotic use; antibiotic resistance; knowledge; attitude; practices; Syria